2020
DOI: 10.1002/ejic.202000133
|View full text |Cite
|
Sign up to set email alerts
|

Impact of H2 and Consecutive H2O2 Exposures on the Oxidative Dissolution of (U1–xGdx)O2 Pellets Under Deep Repository Conditions for Spent Nuclear Fuel

Abstract: The reactivity of H 2 O 2 towards (U 1-x Gd x )O 2 (x = 0.03, 0.045, 0.08) in the presence of H 2 was studied experimentally to assess the effect of H 2 on oxidative dissolution of Gd-doped UO 2 under deep repository conditions for spent nuclear fuel. Gd-doped UO 2 was chosen as a model substance for spent nuclear fuel due to its chemical similarity but low radiotoxicity. While H 2 O 2 is a radiolysis product capable of driving fuel matrix dissolution, H 2 , which is expected to evolve mainly through the corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…15 Electrochemical studies have indicated that catalytic decomposition of H 2 O 2 on UO 2 requires the presence of uranium in higher oxidation state than +IV 16 and recent studies of H 2 O 2 -induced leaching of UO 2 have shown that the redox reactivity of UO 2 (towards H 2 O 2 ) decreases with H 2 O 2 exposure and that this trend is accompanied by a change in the uranium oxidation state even under conditions where dissolution of U(VI) is favoured. 17,18 To better understand these trends, alternative experimental methods are called for. An interesting approach with potential to provide additional mechanistic insights is to expose uranium oxide films of well controlled oxidation state to water plasma in vacuum systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 Electrochemical studies have indicated that catalytic decomposition of H 2 O 2 on UO 2 requires the presence of uranium in higher oxidation state than +IV 16 and recent studies of H 2 O 2 -induced leaching of UO 2 have shown that the redox reactivity of UO 2 (towards H 2 O 2 ) decreases with H 2 O 2 exposure and that this trend is accompanied by a change in the uranium oxidation state even under conditions where dissolution of U(VI) is favoured. 17,18 To better understand these trends, alternative experimental methods are called for. An interesting approach with potential to provide additional mechanistic insights is to expose uranium oxide films of well controlled oxidation state to water plasma in vacuum systems.…”
Section: Introductionmentioning
confidence: 99%
“…1,[18][19][20][21][22] Some studies were made by continuously exposing uranium oxide to low steadystate concentrations of oxidants produced by irradiating suspensions of uranium oxide or pellets immersed in aqueous solution. 8 Other studies focused on the leaching of pellets ( pure or doped with non-radioactive isotopes of fission products) [23][24][25][26][27] and even of thin films. 18,28,29 The impact of dose rate, pH, temperature, oxidant or reductant concentration/pressure, bicarbonate and other groundwater constituents, have been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…18,28,29 The impact of dose rate, pH, temperature, oxidant or reductant concentration/pressure, bicarbonate and other groundwater constituents, have been assessed. 14,19,25,26,[30][31][32] During the last decade, considerable progress has been made in the use of surface spectroscopy to study thin films, including uranium oxide films under UHV conditions. 18,28,33 Very recently, X-ray Photoelectron Spectroscopy (XPS) and UV Photoelectron Spectroscopy (UPS) were used to study changes in uranium oxide thin films exposed to O 2 , H 2 and H 2 O plasmas.…”
Section: Introductionmentioning
confidence: 99%